Alcohol drinking and the risk of colorectal adenoma: a dose–response meta-analysis. Issue 4 (July 2015) - Ben, Qiwen; Wang, Lifu; Liu, Jun; Qian, Aihua; Wang, Qi; Yuan, Yaozong
Abstract : The International Agency for Research on Cancer concluded that alcohol consumption was positively related to colorectal cancer. However, the association between alcohol consumption and colorectal adenoma (CRA), the established precancerous lesion of colorectal cancer, remains unclear. We identified studies from a literature search of MEDLINE, EMBASE, and ISI Web of Science through 31 October 2013, and by searching reference lists of pertinent articles. Summary relative risks with 95% confidence intervals were calculated using a random-effects model. A total of 30 studies with 26 145 incident CRA cases were included. Overall, an increase of 25 g (two drinks) per day of alcohol consumption was related to an increased risk of CRA (summary relative risk=1.27, 95% confidence interval: 1.17–1.37). There was considerable heterogeneity between studies not explained by study design, sex, geographic location, publication year, site or size of the lesions, type of adenoma, number of cases, endoscopic assessment, or adjustment for main confounders. The positive association was evident for both men and women and for colonic adenoma, but not for rectal adenoma. Increased alcohol consumption is associated with an increased risk of CRA for both men and women and for adenoma in the colon, but not in the rectum.